2014
DOI: 10.1371/journal.pone.0102185
|View full text |Cite
|
Sign up to set email alerts
|

Embryonic miRNA Profiles of Normal and Ectopic Pregnancies

Abstract: Our objective was to investigate the miRNA profile of embryonic tissues in ectopic pregnancies (EPs) and controlled abortions (voluntary termination of pregnancy; VTOP). Twenty-three patients suffering from tubal EP and twenty-nine patients with a normal ongoing pregnancy scheduled for a VTOP were recruited. Embryonic tissue samples were analyzed by miRNA microarray and further validated by real time PCR. Microarray studies showed that four miRNAs were differentially downregulated (hsa-mir-196b, hsa-mir-30a, h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
24
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(26 citation statements)
references
References 33 publications
2
24
0
Order By: Relevance
“…miR-873 was previously shown to be among five miRNAs downregulated in EP in a miRNA microarray comparison of pregnancy derived tissues from patients with EP and those with voluntary termination of pregnancy (VTOP) [24], which is consistent with the results of the present study. However, Dominguez et al showed that miR-223 was upregulated in EP, which differs from our results showing that miR-223 expression was significantly lower in EP than in SA.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…miR-873 was previously shown to be among five miRNAs downregulated in EP in a miRNA microarray comparison of pregnancy derived tissues from patients with EP and those with voluntary termination of pregnancy (VTOP) [24], which is consistent with the results of the present study. However, Dominguez et al showed that miR-223 was upregulated in EP, which differs from our results showing that miR-223 expression was significantly lower in EP than in SA.…”
Section: Discussionsupporting
confidence: 92%
“…In the study by Dominguez et al the upregulation of miR-223 was further validated by real-time PCR in a larger sample of embryonic tissues from EP and VTOP, and it was further shown to target GALNT1, a gene in the mucin biosynthesis pathway. Nevertheless, the study by Dominguez et al did not compare EP and SA [24]; therefore, whether the results of the two studies are in accordance is difficult to determine. Zhi et al showed that miR-223 was shown to inhibit bladder cancer cell migration and invasion by downregulating its target ZEB1 [25].…”
Section: Discussionmentioning
confidence: 99%
“…MiRNAs are small, non-coding RNAs that can modulate (mainly repress) gene/protein expression, primarily via interaction with seed regions at the 3' untranslated region (3'-UTR) of target genes, thereby promoting mRNA degradation or Kisspeptin and miR-324-3p in Ectopic Pregnancy preventing protein translation (26). Deregulation of miRNA expression in embryonic/ placental tissues and the fallopian tube has been reported in EP (27)(28)(29). These studies have surfaced changes in the expression patterns of miRNAs of the let7 family, as well as mir-132, miR-145, miR149, miR-182, miR-196, miR-223, and miR-424 in ectopic implantation; yet, the putative mechanistic implications for these alterations are yet to be elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…Hsa-miR-487b is more widely expressed in endothelial and muscle cells in humans and mice, including in cancer cells464748. Hsa-miR-1288 is upregulated in ectopic pregnancy patients49 and associated with the progression of colorectal cancer50. Mmu-miR-743a is expressed in mouse brain and testis and has possible roles in oxidative stress and neurodegeneration5152.…”
Section: Discussionmentioning
confidence: 99%